PENERAPAN TERAPI BEKAM KERING PADA PASIEN NYERI BAHU DI RUMAH SEHAT ZEIN HOLISTIC THERAPY MAKASSAR - Rika Yunus; Sunarti; Samsualam; Eliati Paturungi (CV. ADIBA AISHA AMIRA, 2025)
Frozen shoulder, or shoulder pain, is stiffness of the glenohumeral joint, with limited passive and active movement and pain. In passive movement, mobility is limited to the capsular pattern, with external rotation being the most limited, followed by abduction and internal rotation. To obtain an overview of the application of wet cupping therapy for shoulder pain in Mrs. S at the Zein Holistic Therapy Clinic in Makassar. This case study was conducted on Mrs. S with shoulder pain and acute pain nursing problems on 20 August 2025 at the Zein Holistic Therapy Clinic in Makassar City. The nursing diagnosis that can be established based on the results of the assessment of Mrs. S is acute pain related to physical injury agents. The outcome of this activity was the implementation of a nursing care plan using SIKI, specifically pain management. Based on the results of the implementation and evaluation of cupping therapy on the reduction of right shoulder pain in Mrs. S at Zein Holistic Therapy Makassar Health Centre, a decrease in the right shoulder pain scale was observed, from a pain scale of 3 to a scale of 1.